2024
DOI: 10.1039/d4tb00171k
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical investigation of liposome systems decorated with bioconjugated copolymers in the presence of amantadine

Rosendo Pérez-Isidoro,
Alejandra Gabriela Valdez-Lara,
Alma Jessica Díaz-Salazar
et al.

Abstract: Liposome-based technologies derived from lipids and polymers (e.g., PEGylated liposomes) have been recognized by their medical applications in nanomedicine. However, since such systems represent myriad challenges and may promote immune...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
(120 reference statements)
0
1
0
Order By: Relevance
“…35–37 It has been reported that the drop evaporation process leads to the assembly of phospholipid mixtures for liposome preparation 35 and we have taken advantage of this methodology to successfully assemble biohybrid systems as described in previous works. 37–39 Here, to obtain DMPC/SARMs films, DMPC, and SARMs were weighted and hydrated together with deionized water at 40 °C under stirring (100–1000 rpm) and mixed for 5 h (1000 rpm) at 40 °C. After that, droplets of the DMPC/SARMs suspension were subjected to a drop evaporation process to generate DMPC/SARMs films.…”
Section: Methodsmentioning
confidence: 99%
“…35–37 It has been reported that the drop evaporation process leads to the assembly of phospholipid mixtures for liposome preparation 35 and we have taken advantage of this methodology to successfully assemble biohybrid systems as described in previous works. 37–39 Here, to obtain DMPC/SARMs films, DMPC, and SARMs were weighted and hydrated together with deionized water at 40 °C under stirring (100–1000 rpm) and mixed for 5 h (1000 rpm) at 40 °C. After that, droplets of the DMPC/SARMs suspension were subjected to a drop evaporation process to generate DMPC/SARMs films.…”
Section: Methodsmentioning
confidence: 99%